2023
DOI: 10.3390/healthcare11121766
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes toward Human Papillomavirus and Vaccination: A Survey among Nursing Students in Saudi Arabia

Sally Mohammed Farghaly Abdelaliem,
Abeer Mohammed Kuaia,
Afnan Ahmed Hadadi
et al.

Abstract: Introduction: One of the most prevalent conditions affecting the vaginal organs is the human papilloma virus (HPV). Human papillomavirus (HPV) knowledge and attitudes have been the subject of numerous studies in Saudi Arabia. However, there are only a few studies that have examined university students’ attitudes and knowledge of the human papillomavirus and the vaccine that is associated with it. Aim: To predict the level of knowledge and attitudes regarding HPV and its related vaccine among undergraduate nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…Moreover, their direct involvement in patient care enhances their focus on disease prevention, which in turn further solidifies the transition from knowledge to the intention to vaccinate. In light of these findings, it is recommended to further enhance public health and preventive medicine curricula, with a particular focus on comprehensive training about HPV and its vaccines (33,34). Teaching hospitals should organize targeted health promotion activities, such as workshops and lectures, aimed at increasing medical trainees' awareness of the importance of HPV vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, their direct involvement in patient care enhances their focus on disease prevention, which in turn further solidifies the transition from knowledge to the intention to vaccinate. In light of these findings, it is recommended to further enhance public health and preventive medicine curricula, with a particular focus on comprehensive training about HPV and its vaccines (33,34). Teaching hospitals should organize targeted health promotion activities, such as workshops and lectures, aimed at increasing medical trainees' awareness of the importance of HPV vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies conducted in several countries have consistently indicated that participants have insufficient information about HPV and vaccination. The most influential factors contributing to this lack of understanding are the participants' level of education and age [12][13][14][15].…”
Section: Figure 2: Proportion Of Good Knowledge Level and Poor Knowle...mentioning
confidence: 99%